Особливості визначення змісту договору найму будівлі або іншої капітальної споруди - Позов, Ілля Ілліч; Позов, Илья Ильич; Pozov, Iliia I. (My University, 2016)
Стаття присвячена дослідженню змісту договору найму будівлі або іншої капітальної споруди. Визначаються особливості прав та обов’язків сторін договору. У статті проаналізована природа та особливості переважних прав за договором найму будівлі (споруди). Виявлені недоліки в правовому регулюванні договору найму будівлі або іншої капітальної споруди, внесені пропозиції по їх усуненню та вдосконаленню цивільного законодавства України.

Статья посвящена исследованию содержания договора найма здания или другого капитального сооружения. Определяются особенности прав и обязанностей сторон договора. В статье проанализирована природа и особенности преимущественных прав по договору найма здания (сооружения). Выявленные недостатки в правовом регулировании договора найма здания или другого капитального сооружения, внесены предложения по их устранению и совершенствованию гражданского законодательства Украины.

The thesis is devoted to the research of the essence of contract of lease of a building or other capital facility. In this thesis on the ground of the current legislations and practice of its application the attitudes are analysed, which arise at the concluding, fulfilment and discontinuance of the lease contracts. The author analyzed the rights and responsibilities of the parties to the contract, defined building and other capital facilities. The contents and legal nature of the contract of lease, essential conditions, the legal status of the participants of contractual legal relationships, responsibility of the parties for default or inadequate fulfilment of the lease arrangements of state and municipal property are analysed. The considerable attention in article is allocated to mining of the proposals on advancing the Act of Ukraine «About the lease of state and municipal property», and also other statutory acts, which regulate the contracts of hiring (lease). The author has revealed the disadvantages in the legal regulation of the contract of lease of a building or other capital facility and has formulated some propositions on elimination and perfection of civil legislation in this field.
Позов І. І. Особливості визначення змісту договору найму будівлі або іншої капітальної споруди / І. І. Позов // Часопис цивілістики. – 2016. – Вип. 20. – С. 121-126.
Keywords: договір найму будівлі або іншої капітальної споруди; оренда; орендне зобов’язання; наймодавець; наймач; договор найма здания или другого капитального сооружения; аренда; арендное обязательство; наймодатель; наниматель; the contract of lease of a building or other capital facility; the lease; the lease obligation; the lessor; the lessee